Atividade da enzima NTPDase1 em linfócitos de pacientes em tratamento para leucemia linfoblástica aguda (LLA): alteração na hidrólise do ATP e ADP extracelulares. - Morsch, André Luis Bittencourt (2006)
The NTPDase1 (E.C. 3.6.1.5, apyrase, CD39, ecto-ATP-diphosphohydrolase) enzymatic activity, which is responsible for hydrolyzing ATP and ADP nucleotides, was verified in lymphocytes from 56 patients under treatment for acute lymphoblastic leukemia (ALL) and from 33 healthy subjects. Patients were divided into 3 groups: remission induction (RI), remission maintenance (RM) and out-oftreatment (OT). It had been verified, in each group, the influence of the recurrence risk (high or low) on the enzymatic activity. The RM group was then subdivided by the amount of time they had been in remission maintenance (0-30, 31-60 and 61-84 weeks). Results demonstrated that the ATP hydrolysis from lymphocyte NTPDase1 is altered in the groups studied (F (3,84)=100.34; p<0.01) in relation to the controls, and that it is reduced in both RI and RM groups, while enhanced in OT group. The recurrence risk did not influence ATP hydrolysis in none of the groups. Furthermore, it has been found a significant variation at the NTPDase1 activity to ATP hydrolysis during RM phase (F (2,17)=11.22; p=0.01), being higher in the first 30 weeks, and subsequently reduced. ADP hydrolysis by NTPDase1 activity was also significantly reduced in both the RI and RM groups, but similar to the controls in OT (F (3,69)=59.05; p<0.01). It has not been verified any influence of the recurrence risk on ADP hydrolysis. Furhermore, NTPDase1 using ADP as substrate has shown to be constant during RM phase (F (2,13)=2.40; p=0.130). The alteration on ATP and ADP hydrolysis on lymphocytes of ALL patients is in agreement to the characteristics found in this pathology. Thus, our results corroborate the role of adenine nucleotides, ATP in special, in the immune system, as signaling molecules, and the importance of the NTPDase1 to maintain constant the extracellular levels of these nucleotides. However, more studies are necessary to better understand the role of adenine nucleotides and NTPDase1 in the immunodeficiency and citotoxicity observed in treated ALL patients.